2008
DOI: 10.1002/art.23561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoids on weight change during the treatment of Wegener's granulomatosis

Abstract: Objective. Weight gain is a side effect of glucocorticoid (GC) use, but the natural history and health implications of changes in weight that occur during the treatment of inflammatory disease are not understood. Methods. We evaluated data from the Wegener's Granulomatosis Etanercept Trial. Patients were categorized according to clinical outcome at 1 year: remission (no disease flares), single flare, or multiple flares. Risk factors for gaining >10 kg were examined in multivariate models. Results. Weights at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 34 publications
5
38
1
Order By: Relevance
“…In contrast, a number of GC-driven genes may also contribute to the anti-inflammatory effect (25). CpdA was previously shown not to support transactivation of GRE-dependent promoters (8).…”
Section: Cpda Induces Selective Transrepression Versus Transactivatiomentioning
confidence: 97%
“…In contrast, a number of GC-driven genes may also contribute to the anti-inflammatory effect (25). CpdA was previously shown not to support transactivation of GRE-dependent promoters (8).…”
Section: Cpda Induces Selective Transrepression Versus Transactivatiomentioning
confidence: 97%
“…Some studies report no weight gain compared to controls in the short term up to 3-month treatment duration, but most long-term studies up to 2 years of OCS treatment describe weight gain that varies from a mean of 3 to 11 kg. A study on Wegener's granulomatosis showed no correlation between the dose of OCS and the amount of weight gain [57]. In some circumstances, OCSs are prescribed to patients with cancer cachexia to favor weight gain [58].…”
Section: Management Of Systemic Inflammationmentioning
confidence: 99%
“…Furthermore, weight gain may increase the risk of cardiovascular events in vasculitis. It has been demonstrated recently that patients with Wegener's granulomatosis gained 7·3% weight during the first year after diagnosis and approximately 20% of the patients gained more than 10 kg in the first year of treatment [59]. However, compared with the background population the number of patients with obesity does not seem to be increased [30,50].…”
Section: Pathophysiology Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 99%